1998
DOI: 10.1023/a:1005928814521
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of development of dimethylbenz(a)anthracene (DMBA)-induced mammary tumors in the rat by the new nonsteroidal antiestrogen EM-800 (SCH57050)

Abstract: The effect of EM-800, a new non-steroidal antiestrogen having pure antiestrogenic activity, was studied on chemical carcinogenesis induced by dimethylbenz(a)anthracene (DMBA) as well as on serum lipids and bone mass in the rat. Treatment with EM-800 orally, once daily, for 282 days (9 months), starting 3 days before DMBA administration, decreased the incidence of tumors from 95% in control animals to 60% (p < 0.01), 38% (p < 0.01), and 28% (p < 0.01) at the daily doses of 25 microg, 75 microg, and 250 microg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 55 publications
2
24
1
1
Order By: Relevance
“…11,12 The present study extends these ®ndings by demonstrating that treatment of OVX rats with EM- HCl is at least as effective as estrogen replacement therapy in reverting obesity and its related lipid and glucoseainsulin abnormalities induced by OVX. Estrogen removal through OVX profoundly altered energy balance and lipid metabolism, as previously described by us and others 4 ± 7,19,20 In brief, OVX increased energy intake and food ef®ciency, which resulted in a larger deposition of body energy, mainly in the form of fat.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…11,12 The present study extends these ®ndings by demonstrating that treatment of OVX rats with EM- HCl is at least as effective as estrogen replacement therapy in reverting obesity and its related lipid and glucoseainsulin abnormalities induced by OVX. Estrogen removal through OVX profoundly altered energy balance and lipid metabolism, as previously described by us and others 4 ± 7,19,20 In brief, OVX increased energy intake and food ef®ciency, which resulted in a larger deposition of body energy, mainly in the form of fat.…”
Section: Discussionsupporting
confidence: 74%
“…Such hypolipidemic actions have been reported recently for the prodrug EM-800. 12 In that study performed in fed animals, EM-800 was shown to be frankly hypotriglyceridemic, contrary to the neutral effect of EM-652.HCl observed here in fasted animals. It is most likely that the hypotriglycemic action of EM-652.HCl was masked in the present study by the rather long fasting period imposed on the animals before blood sampling.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Raloxifene (Ral), on the other hand, has less oestrogenic effects on uterus, but the same beneficial effects on bone and lipid metabolism (Delmas et al, 1997;Barrett-Connor et al, 1999;Cohen et al, 2000) while it is an antagonist of oestrogen action in the breast (Gottardis and Jordan, 1987;Cummings et al, 1999). Other SERMs like idoxifene (Idox) (Chander et al, 1991;Nuttall et al, 1998), GW 5638 (Willson et al, 1994(Willson et al, , 1997Connor et al, 2001) and EM 800 (Luo et al, 1998;Labrie et al, 1999;Martel et al, 2000) are different from tamoxifen and based on their activity in the rodent uterus are more closely related to raloxifene. Resveratrol (Res) does not formally belong to the SERM family, because it is a phytoestrogen found in the plants (Jang et al, 1997), however Res has similar in vivo characteristics to the SERMs (Mizutani et al, 2000;Bhat and Pezzuto, 2001;Wu et al, 2001).…”
mentioning
confidence: 99%